Progress in pharmacological pain treatment with opioid analgesics - Leppert, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2009)
The role of opioids in pharmacological cancer pain treatment is essential, especially strong opioids – in Poland morphine, fentanyl, buprenorphine, methadone and recently oxycodone are available. Currently weak opioids are infrequently used worldwide; however, in Poland (tramadol and dihydrocodeine) and in Germany (tramadol) play a significant role in moderate cancer pain treatment. Weak opioids’ role in education and easier availability of tramadol are emphasized. Combining weak or strong opioids with non-opioids and adjuvant analgesics (co-analgesics) improves analgesia. Opioid switching (rotation) plays an important role in patients with poor analgesia and intense adverse effects of opioid. Combining two or more opioids (semi-switch) remains controversial but more studies support such an approach. Opioid pharmacokinetic and pharmacodynamic interactions should be emphasized as they may impair analgesia and intensify opioid adverse effects. In this paper cancer pain treatment rules and properties of tramadol, codeine, dihydrocodeine, morphine, fentanyl, methadone, oxycodone, buprenorphine, hydromorphone and tapentadol are discussed